Programming of the Training Process for Qualified Female Volleyball Players in the Preparatory Period of the Annual Training - Natalia Shchepotina; Viktor Kostiukevych; Inna Asauliuk; Svitlana Dmytrenko; Vadym Adamchuk; Volodymyr Yakovliv; Tamara Chernyshenko (Physical Education Theory and Methodology)
Objectives. The study aimed to experimentally prove the efficiency of building structural formations of the training process for qualified female volleyball players within the preparatory period of the annual training cycle on the basis of programming.